La contaminación del suelo por efectos de la basura frente a los derechos constitucionales a vivir en un habitad seguro y saludable, en los barrios Nueva Esperanza, Los Esteros y Providencia de la ciudad de Machala, en el año 2011. - Naranjo Neira, Romina Sofía (2013)
The main objective of this thesis is to determine how it affects soil pollution by garbage machaleño inhabitant in their right to live in a safe and healthy habitat, pollution-free while proposing the full Provincial Council of El Oro, reform the ordinance regulating decentralized management of environmental competition. Machala, has not escaped pollution, like the rest of Ecuador and view it in the new Constitution of 2008, Article 30 guarantees the right to live in a safe and healthy habitat, and adequate housing and dignity regardless of their social and economic situation. It's been several years and nothing has been done to this inalienable right is met in the sectors taken apara this research work, Nueva Esperanza, Los Esteros, and Providence, where wastes and residues are present in the streets, they are They break down and damage the soil, which cause severe environmental problems.